Nonlinear vibration analysis of cantilever beams: Analytical, numerical and experimental perspectives - Qamar Abbas; Rab Nawaz; Haseeb Yaqoob; Hafiz Muhammad Ali; Muhammad Musaddiq Jamil (Partial Differential Equations in Applied Mathematics)
This study investigates the vibrational behavior of a mild steel cantilever beam with and without an attached end mass using experimental, numerical, analytical, and computational methods. Vibrational frequencies were determined using LABVIEW, MATLAB, and SOLIDWORKS, with analytical results derived from Euler-Bernoulli beam (EBB) theory. Experimental results closely matched MATLAB simulations, with an average percentage error of 1.44%, but showed a 14.44% deviation from analytical results due to neglected accelerometer mass. Findings highlight the importance of precise modeling, accounting for factors like damping and mass effects, to achieve accurate results. The study underscores the significance of resonant frequency identification in mitigating vibration failures in engineering systems.